Polar Bear (Ursus Maritimus) Foraging Ecology in the Western Canadian Arctic - Florko, Katie Rae Nettie (2018)
Climate change has led to abrupt declines in sea ice over the past three decades. Polar bears (Ursus maritimus) rely on sea ice as their primary habitat to hunt marine mammal prey. Due to their position at the top of the Arctic marine food web, polar bear foraging patterns can provide insights on ecosystem structure and function both spatially and temporally. This thesis used quantitative fatty acid signature analysis (QFASA) to estimate the diets, and adipose tissue lipid content to estimate the body condition, of polar bears in three western Canadian Arctic subpopulations: Northern Beaufort Sea, Southern Beaufort Sea, and Viscount Melville Sound. This thesis identified spatial, temporal, and intraspecific variation in the relationships between sea ice conditions, and polar bear diet and body condition. Polar bears with the greatest ecological constraints on diet composition may be most vulnerable to climate-related changes in ice conditions and prey availability.